Preparation of PVA/ME/β-CD and PVA/ME Nanofibers by Electrospinning and Their Activity as a Drosophila melanogaster Attractant - Islamiyah, Anisalia Nur; Cahyono, Edy (Universitas Negeri Semarang, 2021)
Nanofibers are fibers with diameters in the nanometer range. In this study, PVA/ME and PVA/ME/β-CD nanofibers membrane are made by electrospinning method to determine the effect of matrix composition on the characteristics of the nanofibers and their activity as a Drosophila melanogaster attractant. PVA, Methyl Eugenol 98%, and β-Cyclodextrin were used for the electrospinning process. To get the best fibers morphology, the concentration of the sample was varied β-cyclodextrin (β-CD) (30% and 61%), methyl eugenol (5%, 10%, and 12%). The PVA concentration was prepared (was kept) at 12%. The ratio of β-CD and methyl eugenol was set at 1:1; 1:2; and 2:1. The electrospinning parameters were adjusted as 15 kV applied voltage, 10 cm tip-to-collector distance, and 0.5 mm inner diameter of the metallic needle. The average diameter of nanofibers PVA is 92 ± 890 nm. The average diameter of nanofibers PVA/ME is 95±10 nm. The average diameter of nanofibers PVA/ME/β-CD is 100 ± 150 nm. The result of IR spectra shows that PVA and β-CD matrix can trap methyl eugenol compounds as seen from the groups of C=C, –OCH3, and –CH=CH2. Attractant test showed that nanofiber PVA/ME/β-CD is the best product of nanofiber because it has the smallest number of beads and has the maximum activity that can trap the fruit flies with a total amount of 71 flies in a week